Revisiting sports talent identification: A meta analysis - Kusdinar, A.; Abdullah, A. G.; Ma`mun, A.; Rusdiana, A. (Journal of Engineering Science and Technology, 2021)
Talent identification is currently an option for stakeholders in sports to determine athletes who have talent and have the opportunity to succeed in the future. This is still being debated and proven through ongoing studies. The purpose of this paper is to conduct a Systematic Literature Review is to find answers to the following questions: (1) What methods are used in TI research? (2) What are the consideration criteria used in TI? (3) Which sports has been researched for talent search? From the SLR results, it was found that the sports that often used talent identification were football, rugby, and basketball. While the dominant criteria used in talent identification are physical, anthropometric, technical and maturity. Talent identification research is often in the form of correlation, regression and experimental studies using MANOVA. The contribution of the SLR results is to discover the novelty of talent identification research in terms of sports, criteria, and methods used. Meanwhile, from the practical side, this paper will be useful for developing a talent identification model that can be applied and helping volleyball trainers to determine talented athletes